Treatment of orofacial granulomatosis: a case report - Badshah, Maaz B. (J Med Case Rep, 2017)
BACKGROUND: Orofacial granulomatosis is a relatively recent term coined by Wiesenfield et al. in 1985 to define granulomatous lesions of oral mucosa without intestinal involvement. When it presents in a triad encompassing facial nerve palsy, lip swelling, and fissured or furrowed tongue it is called Melkersson–Rosenthal syndrome while monosymptomatic or oligosymptomatic forms are referred to as granulomatous cheilitis. It is an uncommon clinicopathologic entity which is distinct from classic Crohn’s disease. The NOD2 variant which is commonly associated with Crohn’s has not been shown to have any association with orofacial granulomatosis. CASE PRESENTATION: We present a case of a 31-year-old white man who had painful swelling of the lip with oral ulcers and difficulty eating for 2 to 3 years. He was diagnosed as having granulomatous cheilitis based on characteristic biopsy findings. There was serologic evidence of Crohn’s disease with anti-Saccharomyces cerevisiae antibodies. However, he was not found to have any gastrointestinal involvement based on computed tomography enterography, and upper and lower endoscopies. He failed to respond to nonsteroidal anti-inflammatory drugs, steroids, and dapsone therapy but responded well to high doses of infliximab. CONCLUSIONS: Our case questions whether granulomatous cheilitis really exists or is it simply a variant of Crohn’s disease with only oral presentation. Our patient did not have symptoms of Crohn’s disease; moreover, endoscopic studies and computed tomography enterography were unremarkable for evidence of intestinal involvement. Our case is also the first reported case where high-dose infliximab alone has been used with sustained response for approximately 8 months. In conclusion, more research is needed to assess the underlying pathology as well as ideal treatment options for patients with orofacial granulomatosis. We propose that high-dose infliximab should be considered in patients who do not respond to traditional therapies.